UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN PERANGKAT PEMBELAJARAN MELALUI SUVERVISI AKADEMIK DI SMP NEGERI 05 KABUPATEN TEBO TAHUN AJARAN 2019/2020 - YUSRI YUSRI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims: 1) To find out the steps for implementing Academic Supervision activities in preparing the Learning Implementation Plan (RPP) to improve teacher professional competence for teachers at SMP Negeri 05 Tebo Regency in carrying out learning. 2) To find out the increase in teacher competence at SMP Negeri 05 Tebo Regency in the odd semester of the 2019/2020 academic year in Preparing Learning Implementation Plans (RPP) through Academic Supervision activities. The subjects of this study were all teachers of SMP Negeri 05 Tebo Regency in the odd semester of the 2019/2020 school year. This research is School Action Research (PTS) which consists of two cycles, each cycle includes the stages of planning, implementation, observation, and reflection. The data analysis technique used is comparative descriptive. From the results of the study it can be concluded that: 1) The steps for implementing Academic Supervision in order to improve the professional competence of teachers in preparing lesson plans at SMP Negeri 05 Tebo Regency are as follows: (a) Delivering announcements to teachers about the implementation of Academic Supervision activities regarding the preparation of lesson plans; (b) Prepare guidance materials in the form of implementation of learning accompanied by simulations; (c) Preparing Academic Supervision instruments; (d) Carry out Academic Supervision activities without disturbing learning activities; and e) Carrying out observations in the classroom when learning activities are carried out by the teacher; and 2) Academic Supervision can improve the professional competence of teachers of SMP Negeri 05 Tebo Regency in preparing lesson plans. This is indicated by the increasing professional competence of teachers both in the preparation and implementation stages. This is indicated by the increase in competency achievement from 69.58 in the initial condition, to 72.81 at the end of Cycle 1 action, and increased to 83.13 in Cycle II action. ABSTRAKPenelitian ini bertujuan: 1) Untuk mengetahui langkah-langkah pelaksanaan kegiatan Supervisi Akademik dalam menyusun Perangkat Pembelajaran Rencana Pelaksanaan Pembelajaran (RPP) untuk meningkatkan kompetensi profesional guru bagi guru di SMP Negeri 05 Kabupaten Tebo dalam melaksanakan pembelajaran. 2) Untuk mengetahui peningkatan kompetensi guru di SMP Negeri 05 Kabupaten Tebo semester ganjil tahun ajaran 2019/2020 dalam Menyusun Perangkat Pembelajaran Rencana Pelaksanaan Pembelajaran (RPP) melalui kegiatan Supervisi Akademik. Subyek penelitian ini adalah semua guru SMP Negeri 05 Kabupaten Tebo semester ganjil tahun ajaran 2019/2020. Penelitian ini adalah Penelitian Tindakan Sekolah (PTS) yang terdiri dari dua siklus, setiap siklusnya meliputi tahap perencanaan, pelaksanaan, observasi, dan refleksi. Teknik analisis data yang digunakan adalah deskriptif komparatif. Dari hasil penelitian dapat disimpulkan bahwa: 1) Langkah-langkah pelaksanaan Supervisi Akademik guna meningkatkan kompetensi profesional guru dalam Menyusun RPP di SMP Negeri 05 Kabupaten Tebo adalah sebagai berikut: (a) Menyampaikan pengumuman kepada guru tentang akan dilaksanakannya kegiatan Supervisi Akademik mengenai penyusunan RPP; (b) Mempersiapkan materi bimbingan berupa pelaksanaan pembelajaran disertai simulasinya; (c) Mempersiapkan instrumen Supervisi Akademik; (d) Melaksanakan kegiatan Supervisi Akademik dengan tidak mengganggu kegiatan pembelajaran; dan e) Melaksanakan pengamatan di kelas saat dilaksanakan kegiatan pembelajaran oleh guru; dan 2) Supervisi Akademik dapat meningkatkan kompetensi profesional guru SMP Negeri 05 Kabupaten Tebo dalam menyusun RPP. Hal ini ditunjukkan dengan meningkatnya kompetensi profesional guru baik dalam tahap persiapan maupun pelaksanaan. Hal ini ditunjukkan dengan meningkatnya ketercapaian kompetensi dari sebesar 69,58 pada kondisi awal, menjadi sebesar 72,81 pada akhir tindakan Siklus 1, dan meningkat menjadi 83,13 pada tindakan Siklus II.